2021
DOI: 10.15430/jcp.2021.26.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Free Fatty Acid Receptor 2 Exacerbates Colonic Adenoma Formation in ApcMin/+ Mice: Relation to Metabolism and Gut Microbiota Composition

Abstract: Free fatty acid receptor 2 (FFAR2) has been reported as a tumor suppressor in colon cancer development. The current study investigated the effects of FFAR2 signaling on energy metabolism and gut microbiota profiling in a colorectal cancer mouse model (Apc Min/+ ). Ffar2 deficiency promoted colonic polyp development and enhanced fatty acid oxidation and bile acid metabolism. Gut microbiome sequencing analysis showed distinct clustering among wild-type, Apc Min/+ , and Apc Min/+ -Ffar2 -/mice. The relative abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The previous research showed the relative abundance of genus Romboutsia , which was clearly increased in the GA-H group, was positively correlated to the body weight and HDL-C and negatively related to TC, TG, LDL-C and ALT [ 44 ]. Moreover, Turicibacter is positively correlated with tryptophan, indole acid, which may regulate tryptophan metabolism [ 45 ]. The present study showed that alcoholism would lead to impaired tryptophan metabolism [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous research showed the relative abundance of genus Romboutsia , which was clearly increased in the GA-H group, was positively correlated to the body weight and HDL-C and negatively related to TC, TG, LDL-C and ALT [ 44 ]. Moreover, Turicibacter is positively correlated with tryptophan, indole acid, which may regulate tryptophan metabolism [ 45 ]. The present study showed that alcoholism would lead to impaired tryptophan metabolism [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In detail, N-acetylcysteinamide and pyruvate are effective scavengers of ROS [ 50 , 51 ] and betaine can improve oxidative defense by significantly increasing the expression of SOD , CAT, Nrf2 and HO-1 [ 52 , 53 ]. Furthermore, betaine can efficiently improve the body weight gain caused by HFD and decrease the content of TC, TG, and malondialdehyde [ 45 ]. It was indicated that high-dose GA intervention may enhance the N-acetylcysteinamide and pyruvate generation to alleviate ROS and lipid metabolism in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies and network pharmacology studies have confirmed that the occurrence of colon polyps and colorectal tumors is closely related to intestinal barrier function, intestinal flora metabolism, and intestinal inflammation [ 17 , 18 ]. Increased tumorigenesis was observed in mice lacking free fatty acid receptor 2 (FFAR2), which is considered due to reduced intestinal epithelial cell (IEC) integrity and an influx of bacteria [ 19 ]. We found that after modeling, at the genus level, the levels of Coriobacteriia, Parvibacter, Limosilactobacillus, Dubosiella, Lactobacillus, Bacilli, and UCG_010 were significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Circadian regulation of LCAD via Sirt3-mediated deacetylation suggests a role in energy production in response to feeding and fasting cycles 35,36,43 and in vitro studies have implicated LCAD as a tumor suppressor in human cancer [17][18][19]44,45 .…”
Section: Physiological Function Of Lcadmentioning
confidence: 99%